Labor taxes and decision about FDI in the EU - Jan Tecl (European Financial and Accounting Journal, 2017)
This paper analyzes the relationship between tax variables and foreign direct investments. There are many studies with analysis of influence of corporate income tax, but only few with focus on individual taxation and social security contributions. The analysis is done for the decision if do FDI or do not do and about decision about amount of FDI. On the decision about realization of FDI has impact GDP per capita of home and partner country and distance between countries. GDP per capita of home country increase probability of location of FDI, GDP per capita and distance decrease the probability of the location of FDI in the partner country. Based on the results, on the amount of FDI have positive impact GDP variables and other variables - e.g. differences in corporate tax rate. Negative impact has distance between countries. The impact of social security payment is not obvious, because it differs based on the fact of average wage of employee (for higher than average earnings the relationship is negative, for average earnings the relationship is positive).
Keywords: F21; H24; 650; FDI; Individual taxation; Taxation